Zinc sulfate and atrazine toxicity to the marine harpacticoid copepod Robertsonia propinqua - Lisa A. Hack; Louis A. Tremblay; Steve D. Wratten; Guy Forrester; Vaughan Keesing (New Zealand Journal of Marine and Freshwater Research, 2008)
Nauplii and adults of Robertsonia propinqua , a marine sediment‐dwelling copepod, were used in 96‐h static range‐finder toxicity tests to assess the lethal concentration at which 50% of test organisms are killed (LC 50 ) by atrazine (a herbicide) and zinc sulfate. Atrazine and zinc sulfate were used at concentrations near LC 50 values published for crustaceans. LC 50 values for R. propinqua nauplii were 1.5 mg/litre for atrazine and 1.7 mg/litre for zinc sulfate, respectively. For R. propinqua adults, the corresponding values were 31.8 mg/ litre for atrazine and 2.7 mg/litre for zinc sulfate. Robertsonia propinqua nauplii were more sensitive than adult life stages to exposure to both compounds, implying that the juvenile life stages are more sensitive to pollutants. These tests provided some evidence that both atrazine and zinc sulfate may be affecting the reproduction of R. propinqua owing to the reduced juvenile survival rates in the acute tests. The data for atrazine and zinc sulfate have important implications for the development of R. propinqua as a bioindicator of aquatic contamination. The range‐finding LC 50 results provide the basis for the determination of a realistic environmental concentration gradient for application in future definitive LC 50 and chronic full life cycle toxicity tests.